Mewariskan Nilai-Nilai Firman Allah Pada Ulangan 6 : 4-9 - Juita Manullang; Yessica Tanjung; Herdiana Sihombing (Jurnal Magistra, 2023)
As Christians today we must pass on the values of God's Word to the younger generation, the main and most important value is loving the Lord God with all our heart, soul and strength. Researchers used qualitative research methods in completing this paper. This research aims to help readers understand test 6: 5.